Factors that influence married/partnered women’s decisions to use contraception in Zambia - Chiziba, Chilochibi; Chewe, Mwimba; Hangoma, Peter (Frontiers in Global Women's Health, 2024)
According to the Demographic and Health Surveys (DHS), Zambia has shown an increasing trend in the percentage of married women who use contraceptives for the past three decades. As of 2018, this percentage increased from 34.2% in 2001 to 40.8% in 2007 and from 45% in 2013 to 48% in 2018. Despite the increasing trend in contraceptive use, the unmet needs remain relatively high. The low percentage of contraception use translates into 20% of women of reproductive age who are either married/partnered and want to stop or delay childbearing but are not using contraception. This study analysed factors other than availability that influence women’s ability to make or influence the decision to use contraception using logistic regression using data from the Zambia 2013/2014 and 2018 DHS. Furthermore, adjusted odds ratios (aOR) and predicted probabilities were estimated using the fitted logistic regression. Data on 8,335 women were analysed, and 13.7% (n =1,145) had their husband as the sole decision-maker for contraception use, while 86.3% (n = 7,189) made the decisions or participated in making the decision. Contrary to most literature, those with primary or secondary school education were less likely to decide than those without education. The data also associates women who contribute to daily household decisions and have a say in deciding to use contraception. Lastly, women using reversible contraception methods, other methods, hormonal methods, and fertility awareness were associated with less likelihood to decide to use contraceptives than those using barrier methods. Women with lower household decision-making powers are less likely to make or influence decisions to use contraception. Consequently, there is a need to prioritise such women in interventions aimed at increasing contraception use decision-making. Furthermore, more studies are required to investigate why uneducated women have a higher probability of deciding to use contraception. Also, the vast odds ratio difference between all other methods compared to barrier methods (condoms) indicates underlying factors that play a role, which warrants further studies.